Primary cCT Imaging Based Clinico-Neurological Assessment—Calling for Addition of Telestroke Video Consultation in Patients With Intracerebral Hemorrhage - Wagner, Andrea; Schebesch, Karl-Michael; Zeman, Florian; Isenmann, Stefan; Steinbrecher, Andreas; Kapapa, Thomas; Baldaranov, Dobri; Backhaus, Roland; Schlachetzki, Felix (Frontiers in Neurology, 2018)
Background and Purpose: Intracerebral hemorrhage (ICH) requires rapid decision making to decrease morbidity and mortality although time frame and optimal therapy are still ill defined. Ideally, specialized neurologists, neurosurgeons, and (neuro-)radiologists who know the patient’s clinical status and their cerebral computed tomography (cCT) make a joint decision on the clinical management. However, in telestroke networks, a shift towards cCT criteria used for decision making can be observed for practical reasons. Here we investigated the ‘reverse correlation’ from cCT imaging to the actual clinical presentation as evaluated by the Glasgow Coma Scale (GCS) and the National Institutes of Health Stroke Scale (NIHSS). Methods: CCT images and basic information (age, sex, and time of onset) of 50 patients with hypertensive and lobar ICH were presented to 14 experienced neurologists and 15 neurosurgeons. Based on this information, the NIHSS and GCS scores were estimated for each patient. The differences between the actual GCS and NIHSS scores and the cCT-based estimated scores were plotted in a bland-Altman plot. Results: The average estimated GCS score mainly based on cCT was 12.4±2.8 (actual value: 13.0±2.5; p=0.100), the estimated NIHSS score was 13.9±9.1 (actual value: 10.8±7.3; p<0.001). Thus, in cCT-based evaluation, the neurological status of patients especially employing the NIHSS was estimated poorer, particularly in patients with lobar ICH. ‘Reverse clinical’ evaluation based on cCT alone may increase the rate of intubation and secondary transferal and neurosurgical treatment. Telestroke networks should consider both, videoassessment of the actual clinical picture and cCT findings to make appropriate acute treatment decisions.